Micah: an international theological commentary - Gignilliat, Mark S. (T&T Clark International Theological Commentary Ser., 2019)
Cover -- Contents -- General Editors' Preface -- Preface -- Micah Commentaries Bibliography -- A Theological Introduction to a Theological Commentary -- Micah in Critical Dress: A Cursory Overview -- Who Is a God Like You? Micah's Theological Witness in the Book of the Twelve: An Introductory Excurses -- 1 Micah 1:1-Prophetic Identities -- 2 Micah 2:1-5-Love Your Neighbor -- 3 Micah 3-Prophetic Recapitulation and Justification -- 4 Micah 4-Between Then and Now -- 5 Micah 5 -- 6 Micah 6 -- 7 Micah 7-Lamenting in Hope -- Index -- Scripture Index.